Rare bird documentation form for Peregrine Falcon at Muskrat Slough, 1981 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1981)
Rare bird documentation form for a Peregrine Falcon at Muskrat Slough in Jones County, IA on April 30, 1981. Epson - sheet feed